2014
DOI: 10.1016/j.renene.2013.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of solar chimney power plant with radiation model

Abstract: a b s t r a c tA three-dimensional numerical approach incorporating the radiation, solar load, and turbine models proposed in this paper was first verified by the experimental data of the Spanish prototype. It then was used to investigate the effects of solar radiation, turbine pressure drop, and ambient temperature on system performance in detail. Simulation results reveal that the radiation model is essential in preventing the overestimation of energy absorbed by the solar chimney power plant (SCPP). The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(31 citation statements)
references
References 27 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…They found that the increase in the power output was higher than the increase in the expenditure of the optimal configuration [177]. Guo et al [178] simulated a new model for a solar chimney power plant that included the solar load, turbine models, and the radiation. Then they evaluated the influences of turbine pressure drop, ambient temperature and solar radiation on the performance of the system.…”
Section: Analytical and Simulation Studiesmentioning
confidence: 99%
“…They found that the increase in the power output was higher than the increase in the expenditure of the optimal configuration [177]. Guo et al [178] simulated a new model for a solar chimney power plant that included the solar load, turbine models, and the radiation. Then they evaluated the influences of turbine pressure drop, ambient temperature and solar radiation on the performance of the system.…”
Section: Analytical and Simulation Studiesmentioning
confidence: 99%
“…In [15] a novel small scale model of solar chimney was investigated experimentally and numerically where the experimental results show that utilization of intensifiers lead to a maximum velocity of 5.12 m/s. The research of [16] presents numerical simulations of a solar chimney power plant with a radiation model wherein the results indicate that the radiation model is essential in preventing the overestimation of energy absorbed by the solar chimney power plant. In [17], a mathematical thermal model for steady state airflow inside a solar chimney power plant based upon the modified Bernoulli equation with buoyancy effects and ideal gas equation are given.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pastohr et al used the Betz limit to calculate the value of the pressure drop for the reverse fan model [17]. The value of the pressure drop was also estimated by using a parametric study [24,26], and an iterative approach [21]. The main advantage of the reverse fan model was to simulate the pressure jump of the turbine with a computationally low cost.…”
Section: Introductionmentioning
confidence: 99%